Massive Hematemesis as Initial Presentation of Advanced Pancreatic Adenocarcinoma - Jonathan Farshadmand; Neyshia Rodriguez; Simon Kashfi; Prachi Mehta (Journal of Clinical Case Reports and Images, 2023)
Pancreatic adenocarcinoma is one of the leading causes of cancer-related death in the United States. Rarely, a tumor at the head of the pancreas can invade adjacent structures to cause a gastrointestinal bleed (GIB). We present a 78-year-old female whose massive upper GIB was the initial presentation of metastatic pancreatic adenocarcinoma. Prior reports have documented GIB in patients with known pancreatic cancer, but in our case, the diagnosis was made after the bleed was controlled, making this presentation rare and associated with a poor prognosis.
Keywords: pancreatic adenocarcinoma gastrointestinal bleed